Increasing the machining productivity of the mortar Breech through automated tool selection - Yevdokymov, Oleksandr; Kolesnyk, Vitalii; Dovhopolov, Andrii; Nekrasov, Yurii; Basov, Vadym; Fadieiev, Viacheslav (Національний технічний університет "Харківський політехнічний інститут", 2025)
In the study, an automated selection of cutting tools and cutting parameters was performed for the turning of the breech component of the stationary smoke mortar of the AEK-902 “Khmara” aerosol system. The AEK-902 is actively used by the Armed Forces of Ukraine to create a dense smoke screen in order to conceal military equipment from enemy visual, infrared, and thermal detection systems. The breech is a critical mortar component subjected to significant mechanical and thermal loads during operation, which imposes high demands on the quality of its manufacturing, geometric accuracy, and wear resistance. An automated selection of cutting tools and cutting parameters for each turning operation of the breech was carried out using specialized software from two leading global manufacturers of cutting tools: Walter GPS (Walter company) and Sandvik Coromant ToolGuide (Sandvik Coromant company). The selection was made taking into account the type of machining, the geometry of the workpiece, material characteristics, and the requirements for accuracy and surface quality. As a result, a nomenclature of tooling (toolholder and insert types) recommended for each specific turning operation was obtained, as well as productive cutting parameters. У дослідженні виконано автоматизований підбір ріжучого інструменту та режимів різання для токарної обробки деталі казенника стаціонарної димової мортири аерозольної системи АЕК-902 «Хмара». АЕК-902 активно застосовується у Збройних Силах України для створення щільної димової завіси з метою маскування військової техніки від засобів візуального, інфрачервоного та теплового виявлення противника. Було проведено автоматизований підбір ріжучого інструменту та параметрів режимів різання для кожного переходу токарної обробки казенника з використанням спеціалізованого програмного забезпечення двох провідних світових виробників ріжучого інструменту: Walter GPS (компанія Walter) та Sandvik Coromant ToolGuide (компанія Sandvik Coromant). Підбір здійснювався з урахуванням типу обробки, геометрії заготовки, характеристик матеріалу, вимог до точності та якості поверхні. У результаті було отримано номенклатуру інструментального оснащення (тип державки та пластини), рекомендовану для кожного окремого переходу токарної обробки, а також продуктивні режими різання.
Підвищення продуктивністі обробки деталі Казенник мортири методом автоматизованого підбору інструменту
Keywords: Breech of the mortar; automated selection; turning; machining; cutting parameters; cutting tool; productivity; Казенник мортири; автоматизований підбір; точіння; механічна обробка; режими різання; ріжучий інструмент; продуктивність